A Statistical Study of EMIC Waves Associated With and Without Energetic Particle Injection From the Magnetotail. Issue 1 (30th January 2019) - Jun, C.‐W.; Yue, C.; Bortnik, J.; Lyons, L. R.; Nishimura, Y.; Kletzing, C.; Wygant, J.; Spence, H.
Abstract: To understand the relationship between generation of electromagnetic ion cyclotron (EMIC) waves and energetic particle injections, we performed a statistical study of EMIC waves associated with and without injections based on the Van Allen Probes (Radiation Belt Storm Probes) and Geostationary Operational Environmental Satellite (GOES; GOES‐13 and GOES‐15) observations. Using 47 months of observations, we identified wave events seen by the Van Allen Probes relative to the plasmapause and to energetic particle injections seen by GOES‐13 and GOES‐15 on the nightside. We separated the events into four categories: EMIC waves with (without) injections inside (outside) the plasmasphere. We found that He + EMIC waves have higher occurrence rate inside the plasmasphere, while H + EMIC waves predominantly occur outside the plasmasphere. Meanwhile, the time duration and peak occurrence rate of EMIC waves associated with injections are shorter and limited to a narrower magnetic local time region than those without injections, indicating that these waves have localized source regions. He + EMIC waves inside the plasmasphere associated with injection are usually accompanied by an increase in H + flux within energies of 1–50 keV through all magnetic local time regions, while most wave events outside the plasmasphere show less relationship with H + flux increase. From these observations, we suggest that injected hot ions are the major driver of He + EMIC waves inside the plasmasphere during active time. Expanding plasmasphere during quiet times can provide broad wave source regions for He + EMIC waves on the dayside. However, H + EMIC waves outside the plasmasphere show different characteristics, suggesting that these waves are generated by other processes. Key Points: A statistical study of EMIC waves associated with and without injections based the Van Allen Probes and GOES satellites is performed The spatial occurrence distributions of the EMIC waves and relationship between EMIC wave activity and energetic H + flux are examined He + EMIC waves are dominantly observed inside the plasmasphere, while H + EMIC waves are predominantly detected outside the plasmasphere